Assessment of the effect of wave device application on morphological changes in organs and cells of irradiated animals - Bebeshko, V.; Homolyako, I.; Grynchyshyn, V. (Experimental Oncology, 2017)
Aim: To study the effect of the Device for wave influence on biological objects on the prevention of the development of acute radiation sickness and chronic radiation syndrome in vivo. Materials and Methods: The studies were performed on white rats irradiated at a dose of 8 Gy. The experimental group of irradiated rats was treated with a wave Device (Patent of Ukraine No. 53568) once, for 2.5 min, 1.5 h after irradiation. Their organs were processed by standard histologic methods. Results: In the demagnetized rats, dystrophic changes in cells and tissues of liver, lungs, kidneys, brain, bone marrow and spleen were insignificant in 60 days compared to the control non-demagnetized group of animals. Conclusion: The Device reduced the magnetic charge of magneto-containing elements and their compounds in the organism of the irradiated animals, and decreased the formation of reactive oxygen species, which play a key role in the development of radiation-induced diseases.